Atlas of fibre fracture and damage to textiles - Hearle, J. W. S. (CRC Press ; Woodhead Pub. in association with Textile Institute, 1998)
This new, retitled, edition of Fibre Failure and Wear of Materials has been updated and expanded to include more examples from work at UMIST (University of Manchester Institute of Science and Technology) in the 1990s and to take account of recent research elsewhere. It contains over 500 new micrographs to add to the 1,000 in the first edition and includes two new sections on forensic and medical studies. Based on over 25 years of research at UMIST, the book is concerned with how fibres fail under stress. Until comparatively recently little was known about the way in which fibres break. In this book about 20 different modes of fibre failure are examined. Case studies have been selected both from the traditional uses of textiles in clothing and in household products, such as sheets, towels and carpets and also from the study of failure in textile structures used in industry and engineering, for example seat belts and ropes. This unique collection of more than 1500 scanning electron micrographs and other pictures for identifying failure modes, together with the accompanying explanatory text, provides fibre scientists, polymer scientists and others working in textile research with a better understanding of fracture mechanisms. The book will also be of interest to forensic scientists and medical specialists using fibre implants. Finally, it will help textile technologists and design engineers to manufacture improved textile products and to use them in ways which will maximise their life span.